Dimensions and Outcome of Experience Quality in Outdoor Dining Casual : The Case of Outdoor Cafe in Indonesia - Karisma Sri Rahayu; Edy Yulianto; Andriani Kusumawati (Sekolah Pascasarjana Universitas Brawijaya, 2019)
This study to determine the effect of experience quality on customer satisfaction and customer loyalty. the relationship between experience quality and customer loyalty indirectly through customer satisfaction is explained in this study. A total of 168 questionnaires were distributed to respondents who already had experience visiting and enjoying food in natural outdoor cafes in Malang, Indonesia. Data was collected by direct survey to respondents and analyzed using the Structural Equation Modeling (SEM) equation and then analyzed with three stages of inferential statistics. The demographics of the respondents were also described in this study. The findings of this study indicate that the emergence of millennial generations has made changes in lifestyle today. The results of hypothesis testing of this study prove that experience quality has a positive and significant influence on customer satisfaction and customer loyalty. Customer satisfaction plays a partial mediating role between experience quality variables and customer loyalty.